Time in ancient Greek literature - Jong, Irene J. F. de.; Nünlist, Rene. (Mnemosyne, Supplements, 2007)
This is the second volume in a series of volumes which together will provide an entirely new history of ancient Greek (narrative) literature. Its organization is formal rather than biographical. It traces the history of central narrative devices, such as the narrator and his narratees,time, focalization, characterization, and space. It offers not only analyses of the handling of such a device by individual authors, but also a larger historical perspective on the manner in which it changes over time and is put to different uses by different authors in different genres. The present volume deals with time: changes in the order of events (analepsis versus prolepsis), the speed of narration (events may be recounted scenically or in the form of a summary), and frequency (events may be recounted once, repeatedly, or not at all).